INSTITUTIONALIZING THE CONSTITUTIONAL QUESTION AUTHORITY IN THE CONSTITUTIONAL COURT AND POSSIBILITY INSTITUTIONALIZING IN SUPREME COURT - Manurung, Saut Parulian; Suhartono, Slamet; Nasution, Krisnadi (Jurnal Hukum Magnum Opus, 2021)
AbstractThis article aims to analyze and discuss the institutionalization of the idea of a constitutional question at the Constitutional Court, and the possibility of its institutionalization at the Supreme Court. The method used is a statutory approach, a conceptual approach, and a comparative approach. This article takes the position of "agreeing" if the idea becomes the authority of the Constitutional Court. However, from a different perspective, this article also discusses the possibility of its institutionalization through the Supreme Court. Institutionalization of the constitutional question at the Constitutional Court can at least be carried out in three ways, namely, by amending the 1945 Constitution of the Republic of Indonesia, revising the Law on the Constitutional Court, and through Jurisprudence. On the other side, as a role model for practice and the regulation of a constitutional question mechanism, the Austrian and German states were taken as an example. While institutionalizing the idea at the Supreme Court, theoretically, this is very prospective when referring to comparative studies with the United States, because the US Supreme Court currently has the authority to examine the constitutionality of laws. The goal, if institutionalized in the Supreme Court, is for the Supreme Court to take part in realizing law and constitutional enforcement.Keyword: Constitutional Court; constitutional question; Supreme CourtAbstrakArtikel ini bertujuan untuk menganalisis dan membahas pelembagaan gagasan persoalan konstitusional di Mahkamah Konstitusi, dan kemungkinan pelembagaannya di Mahkamah Agung. Metode yang digunakan adalah pendekatan statutori, pendekatan konseptual, dan pendekatan komparatif. Pasal ini mengambil posisi “menyetujui” jika gagasan tersebut menjadi kewenangan Mahkamah Konstitusi. Namun, dari sudut pandang yang berbeda, artikel ini juga membahas kemungkinan pelembagaannya melalui Mahkamah Agung. Pelembagaan soal konstitusional di Mahkamah Konstitusi setidaknya dapat dilakukan dengan tiga cara, yakni dengan amandemen UUD 1945, revisi Undang-Undang Mahkamah Konstitusi, dan melalui yurisprudensi. Di sisi lain, sebagai panutan bagi praktik dan regulasi mekanisme persoalan konstitusional, negara Austria dan Jerman dijadikan contoh. Sementara melembagakan gagasan di MA, secara teoritis hal ini sangat prospektif jika mengacu pada studi banding dengan Amerika Serikat, karena MA saat ini memiliki kewenangan untuk memeriksa konstitusionalitas undang-undang. Tujuannya, jika dilembagakan di Mahkamah Agung, agar Mahkamah Agung turut serta mewujudkan penegakan hukum dan konstitusi.Kata Kunci: Mahkamah Agung; Mahkamah Konstitusi; pertanyaan konstitusi